BENTUK TARI JUNJUNGAN BUAY PUUN: REPRESENTASI IDENTITAS KOTA METRO - Zurly, Indah Kharisma (Jurnal Seni dan Pembelajaran, 2023)
The Junjungan Buay Puun Dance was created in 2019 based on the idea of the Metro City Education and Culture Department to create a typical Metro City dance. The aim of this research is to describe the Junjungan Buay Puun dance form which represents the identity of Metro City using qualitative methods and data obtained through observation, interviews and documentation techniques. This research uses Shape theory by Hadi (2012) and Identity theory by Barker (2016). In general, the results of this research show that the form of the Junjungan Buay Puun dance represents the openness of Metro City society towards ethnic diversity in Metro City. The results of this research show that there are 5 forms of dance which represent the identity of Metro City, namely movements consisting of 8 types of movements, namely Tattu Junjung, Tepas TepisKalai, Maccor Ngahelok, Jelang Jalin, Layang Jong Layang, Sanjung Junjung, Laju Tengarei, and Petik Betik , floor patterns, accompaniment or music, clothing arrangements namely Kupiah, Deker Bahu, Papan Jajar Kreasi, Pending, and Kana Rincing, as well as Siger properties which are covered with trays.